2008
DOI: 10.1159/000136652
|View full text |Cite
|
Sign up to set email alerts
|

Can We Discriminate Stroke Mechanisms by Analyzing the Infarct Patterns in the Striatocapsular Region?

Abstract: Background and Aims: The aims of our study were to elucidate the differences in the distribution of acute middle cerebral artery (MCA) infarctions involving the striatocapsular region and to compare those following embolic striatocapsular infarctions with those originating from MCA disease (MCAD). Methods: We prospectively enrolled patients with acute large infarcts located in the lenticulostriate artery territory. Brain coronal diffusion-weighted imaging (DWI) and magnetic resonance angiography were carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
1
3
0
2
Order By: Relevance
“…Since striatocapsular stroke is a rather rare type of ischemia, this also makes for a seemingly limited number of patients in our study. In this respect, this study is in line with other studies, which have studied stroke in this location and have reported on similar or smaller numbers of patients [9,24,25,26]. We cannot exclude that our results have at least been partially influenced by varying degrees of cerebral atrophy in our patients.…”
Section: Discussionsupporting
confidence: 91%
“…Since striatocapsular stroke is a rather rare type of ischemia, this also makes for a seemingly limited number of patients in our study. In this respect, this study is in line with other studies, which have studied stroke in this location and have reported on similar or smaller numbers of patients [9,24,25,26]. We cannot exclude that our results have at least been partially influenced by varying degrees of cerebral atrophy in our patients.…”
Section: Discussionsupporting
confidence: 91%
“…To the best of our knowledge four major pathophysiologic processes have been proposed to cause iSCIs: (1) emboli to the proximal MCA (14, 42); (2) triangular-shaped carotid T occlusion allowing cortical supply (1); (3) extracranial carotid artery occlusion with either presumed emboli to the proximal MCA or hemodynamic alterations leading to deep territory infarction (4, 32); (4) atherosclerotic disease of the MCA with concomitant in situ thrombosis or other isolated MCA abnormalities (dissection, vasculitis) (4, 32, 43). Emboli to the MCA were found to result in iSCI if the peripheral tissue is preserved by an outstanding collateral system, and in combination with/or if the occlusion is of transient nature, which might be due to spontaneous thrombolysis, IV rtPA induced thrombolysis (23) or, as shown here, with ET.…”
Section: Discussionmentioning
confidence: 99%
“…The coronal DWI of lesion distributions could indicate stroke causes and mechanisms in patients with striatocapsular infarctions [16]. However, this is the first study that demonstrates the clinical and imaging differences between the two patterns of the small deep infarcts in the subcortical area by coronal DWI.…”
Section: Discussionmentioning
confidence: 99%